NEW METHOD FOR CONSTRUCTION OF OPTIMAL SCALAR QUANTIZERS FOR LAPLACIAN SOURCE - Peric, Zoran; Nikolic, Jelena; Pokrajac, Dragoljub (International Journal of Computing, 2014)
In this paper we consider methods for computing the necessary parameters when constructing the optimal scalar quantizers for Laplacian source. We investigate two approaches to the problem of finding the sets of optimal parameters. The first approach requires solving the transcendental equations, but provides nearly optimal values of the scalar quantizers’ parameters on successive manner. The proposed approach is an approximation method that linearizes transcendental equations providing simple and fast computing of scalar quantizers’ parameters. We demonstrate that the proposed technique provides parameters values that are very close to the optimal ones.